Analisa Akurasi Dimensi Produk Model Tiga Dimensi (3D) dari Investmen Gypsum Berbasis Layer Manufacturyng Technology - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Layer manufacturing is now becoming one of solution in prototyping of a manufacturing product in order to speed up introduction to market. One method of layer manufacturing technology is using material powder and binder to consolidate the powder into a certain shape. This paper presents the results of experiment on dimension accuracy analysis of a prototype made of powder-water. Material has been used in the research was investment gypsum and water was treated as a binder. Three models with a basic geometry shape as a standard geometric i.e. cube, prism and cylinder, have been used as samples to be analyzed its dimension accuracy. Analysis was carried out by applying statistic method 'One Sample T-test' to compare CAD and models. The results show that there were in agreement between the CAD dimension and models for length. width and height of the cube, and height of the prism and diameter of the cylinder.